IMPROVING THE COMMUNITY ECONOMY BASED ON ISLAMIC PHILANTHROPY IN SOCIAL AND RELIGIOUS INSTITUTIONS - Faridatun Najiyah, Noor Iffatin Nadhifah (JINGJI : Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
This study illustrates the importance of optimizing ZIS activities based on Islamic philanthropy from the perspective of religious morality. Zakat is not only considered as a religious ritual, but also as a moral obligation that goes beyond mere formal actions. LAZIZ demonstrates a commitment to managing ZIS funds professionally, with a focus on using funds for productive businesses aimed at improving community welfare. LAZIZ conducts a careful survey of mustahik to ensure that funds are distributed on target. In addition, LAZIZ applies a consumptive and productive approach in managing ZIS funds, by providing direct assistance and providing business capital through the BUM program.